Factors associated with neonatal death among adolescent mothers - Viviane Maria Gomes de Araujo; Juliana Santana da Silva; Carolina Luiza Bezerra Silva; Maria do Socorro de Oliveira Costa; Emília Chagas Costa; Paulo Germano Frias; Mauro Virgílio Gomes de Barros; Marco Aurélio de Valois Correia Junior (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to analyze factors associated with neonatal death among adolescent mothers. Methods: randomized hospital-based cross-sectional study in a tertiary institution,, data from the Sistema de Informação sobre Nascidos Vivos (Sinasc), (Live Birth Information System), Sistema de Informação sobre Mortalidade (SIM) (Mortality Information System), and medical records. The study population was comprised of 1,341 adolescents aged 10-19 who had assisted childbirth at the institution between 2012 to 2016. The independent variables were sociodemographic characteristics, care, prenatal, childbirth, birth, and newborn's hospitalization, as well as the baby's characteristics. Logistic regression analysis was carried out to assess the association between neonatal death and explanatory variables. Results: the factors associated with death were from the countryside or other States (OR=2.68; CI95% =1.24-5.81), Apgar scores lower than 7 in the 1st (OR= 9.52; CI95% = 4.15-21.81) and the 5th (OR=4.17; CI95%=1.53-11.34) minutes of life; and birth weight less than 999g (OR=13.37; CI95% =3, 64-49.04) and between 1,500 to 2,499g (OR=3.43; CI95%=1.37-8.58). Conclusions: apgar and low birth weight were associated with the neonatal death among adolescent mothers, as well as the fact they come from the countryside and other States. These findings show, in addition to classic risks, potential difficulties for adolescents in having access to healthcare services in their hometown. To reduce the risks, there is a need for restructuring the maternal and child healthcare network and ensure a social protection network for these girls.